2015
DOI: 10.1016/j.joa.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Combined catheter ablation for atrial fibrillation and Watchman® left atrial appendage occlusion procedures: Five‐year experience

Abstract: BackgroundPatients with atrial fibrillation (AF) may benefit from undergoing concomitant interventions of left atrial catheter ablation and device occlusion of the left atrial appendage (LAA) as a two-pronged strategy for rhythm control and stroke prevention. We report on the outcome of combined procedures in a single center case series over a 5-year timeframe.MethodsNinety-eight patients with non-valvular AF and a mean CHA2DS2-VASc score 2.6±1.0 underwent either first time, or redo pulmonary vein isolation (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
58
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(71 citation statements)
references
References 24 publications
11
58
2
Order By: Relevance
“…The Watchman device did not interfere with a repeat ablation. Similar experience had been reported in other single‐ and multicenter studies . The 5‐year outcomes of combination therapy (LAAC with the Watchman device and CA for AF) also indicated the long‐term efficacy and safety .…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…The Watchman device did not interfere with a repeat ablation. Similar experience had been reported in other single‐ and multicenter studies . The 5‐year outcomes of combination therapy (LAAC with the Watchman device and CA for AF) also indicated the long‐term efficacy and safety .…”
Section: Discussionsupporting
confidence: 79%
“…Magnetic resonance imaging assessment of the LAA in an 8‐patient study indicated nonsignificant increase and decrease of LAA diameters and area within 48 hours of and 3 months post‐AF ablation, providing reassurance for concomitant AF CA and LAAC . In fact, the ablation‐first strategy was adopted in several combination studies with implantation of Watchman devices . However, acute and subacute radiofrequency tissue injury presenting as edema in this region might be a deterrent, causing peridevice leak.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, some centers have begun to perform concomitant catheter ablation and WATCHMAN LAA occlusion 3, 4, 5, 6. This strategy has the benefit of providing treatment for symptomatic AF as well as stroke prevention without the need for long-term anticoagulation.…”
Section: Introductionmentioning
confidence: 99%